Enhancing Teacher Readiness: Micro-Teaching Practices During Curriculum Transition at UIN Walisongo Semarang - Nur Asiyah; Atika Dyah Perwita; Jannatin Aliah; Fifi Fifi (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This research report examines micro-teaching implementation in the context of curriculum transition at the Faculty of Tarbiyah and Teacher Training, UIN Walisongo Semarang. The study aims to analyze the design, execution, and evaluation of micro-teaching practices during the shift from the 2013 Curriculum to the Merdeka Curriculum. The significance of this research lies in its focus on preparing future educators to utilize both curricula in their teaching practices effectively. By engaging in micro-teaching, students develop essential teaching skills, enhance their communication abilities, and gain practical experience in classroom management. This study highlights students' challenges and opportunities as they adapt to new educational frameworks, emphasizing the importance of hands-on training in fostering professional competencies. The findings are intended to contribute to developing a micro-teaching guide and serve as a reference for improving micro-teaching practices at UIN Walisongo and beyond. Ultimately, this research underscores the critical role of effective teacher preparation programs in enhancing educational quality and meeting the demands of contemporary teaching environments.